Me, Myself, and I On the Role of Self-Reflection in Adult Education - Henriette Lundgren (Adult Education Research Conference, 2014)
This study builds on contemporary adult learning theories that deal with reflexivity and the construction of self, and its purpose is to explore in an empirical research setting how self-reflection is depicted in three dimensions – cognitively, emotionally, and socially – by participants of workplace training workshops.